IMPROVING LECTURER’S CLASSROOM MANAGEMENT SKILLS FOR QUALITY ASSURANCE IN COLLEGES OF EDUCATIONS IN ENUGU STATE, NIGERIA - EKWE, GABRIEL (UNIZIK Journal of Educational Management and Policy, 2024)
The study centered on improving lecturer’s classroom management skills for quality assurance in colleges of educations in Enugu State. Three research questions and three hypotheses were formulated for the study. The population for the study consists of 704 male lecturers and 640 female lecturers. The sample for this study comprised 135 respondents (71 male lectures and 64 female lecturers). Multi stage sampling technique was adopted. First, simple random sampling technique was used to sample respondents from public colleges of educations in the State. Three expert validated the instrument. Questionnaire as instrument for data collection was designed by the researcher to elicit appropriate information from the respondents. The reliability co-efficient of the instrument was calculated using cronbach Alpha method. Alpha value was found to be 0.79 indicating high reliability of the instrument. Mean score and standard deviation were used to answer the research questions, and t-test statistic was used to test the hypotheses at 0.05 level of significance. Some of the major findings of the study indicated that effective communication enhance lecturers’ classroom management skills for quality assurance in colleges of education in Enugu state. It also revealed that there is great extent to which effective discipline enhance lecturers’ classroom management skills for quality assurance in colleges of education in Enugu State. Based on this, it was recommended that Lecturers’ should adopt different means of communication that will enable students to decode any information pass across to them.